2016
DOI: 10.1038/srep34552
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the contribution of Staphylococcus aureus α-phenol-soluble modulins to biofilm amyloid structure

Abstract: The opportunistic pathogen Staphylococcus aureus is recognized as one of the most frequent causes of biofilm-associated infections. The recently discovered phenol soluble modulins (PSMs) are small α-helical amphipathic peptides that act as the main molecular effectors of staphylococcal biofilm maturation, promoting the formation of an extracellular fibril structure with amyloid-like properties. Here, we combine computational, biophysical and in cell analysis to address the specific contribution of individual P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
82
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(100 citation statements)
references
References 49 publications
11
82
1
2
Order By: Relevance
“…The longer time of the fibrillation is caused by the different aggregation feature of PSMα1 in vitro from PSMs in ECM of biofilm. 37 Control peptides start forming short fibers in diameter of 11.4 ± 1.79 nm and in length of 134.4 ± 59.5 nm on Day 4, and the fibers were continuously elongated till Day 9 with similar diameter of 12.4 ± 0.82 nm (Figure 3a (Figure 3g); however, there is only small aggregates in diameter of 32.28 ± 11.03 nm observed in the TEM images with 800 µg/mL GQDs (Figure 3h).…”
Section: K Porosity Of Biofilm In Png Mediamentioning
confidence: 99%
“…The longer time of the fibrillation is caused by the different aggregation feature of PSMα1 in vitro from PSMs in ECM of biofilm. 37 Control peptides start forming short fibers in diameter of 11.4 ± 1.79 nm and in length of 134.4 ± 59.5 nm on Day 4, and the fibers were continuously elongated till Day 9 with similar diameter of 12.4 ± 0.82 nm (Figure 3a (Figure 3g); however, there is only small aggregates in diameter of 32.28 ± 11.03 nm observed in the TEM images with 800 µg/mL GQDs (Figure 3h).…”
Section: K Porosity Of Biofilm In Png Mediamentioning
confidence: 99%
“…PSMs stimulate inflammatory responses, contribute to biofilm formation and are capable of lysing human cells, including erythrocytes and leukocytes, such as T cells Laabei et al, 2014). Several PSM members were shown to form amyloid fibrils, essential to their activity (Marinelli et al, 2016;Salinas et al, 2018;Schwartz et al, 2012;Tayeb-Fligelman et al, 2017). Amyloids are structured protein aggregates mostly known for their association with systemic and neurodegenerative diseases (Eisenberg and Jucker, 2012;Knowles et al, 2014;Tycko, 2015), but are also involved in various physiological functions in humans and in microbes (Chapman et al, 2002; DePas and Chapman, 2012;Fowler et al, 2005;Hughes et al, 2018;Jacob et al, 2016;Maji et al, 2009;Otzen and Nielsen, 2008;Pham et al, 2014;Schwartz et al, 2012;Soragni et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…They are known to form highly stable cross-β fibrils composed of tightly mated β-sheets, with β-strands oriented perpendicularly to the fibril axis (Eisenberg and Sawaya, 2017;Knowles et al, 2007). PSMα1 and PSMα4 comprise the robust crossβ fibrils, which confer high stability to the bacterial biofilm (Marinelli et al, 2016;Salinas et al, 2018;Schwartz et al, 2012), rendering it a resilient physical barrier against antibiotics and the immune system. However, PSMα3, the most cytotoxic member of the family Cheung, Kretschmer, et al, 2014;Wang et al, 2007), forms unique cross-α fibrils (Tayeb-Fligelman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…PSMs peptides are major determinants and play an important and diverse role in the biofilm matrix in S. aureus [11]. Previous studies have shown that PSMs from S. aureus form functional amyloids that contribute to biofilm integrity and provide resistance to disruption, which is critical to the virulence of medical device-associated infections [6,38]. However, there have been no efforts to date to establish a general picture for the self-assembly of PSMs peptides that brings together all the species in the aggregation cascade.…”
Section: Discussionmentioning
confidence: 99%
“…suggested that the peptides of individual families might display differential self-assembly properties [38]. We first determined the rates of the various microscopic steps (concentration dependent) associated with the aggregation of PSMs peptides.…”
Section: Earlier Computational Analysis Of Psms Sequences (Smallest Smentioning
confidence: 99%